Community Relations Management Based on Gayo Alang Tulung Customs and Community Participation in Junior High Schools - Nora, Hestya Fitri; Iskandar, Iskandar; Yanti, Hera (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze community relations management based on Gayo Alang Tulung customs and its implications for community participation in junior high schools. The study used a qualitative approach with research subjects including Gayo traditional leaders, school community relations managers, and school principals. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis used data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of community relations management based on Gayo Alang Tulung customs has built harmonious communication between schools and the community, both in academic and non-academic activities. Alang Tulung values such as mutual assistance, mutual cooperation, and solidarity are the foundation for strengthening school-community relations, although the involvement of traditional leaders has not been fully optimal. School communication strategies that prioritize transparency, openness, and a persuasive approach have been proven to increase community trust and participation. The conclusion of this study confirms that community relations management based on local customs is effective in increasing community participation and strengthening the school's position as part of the socio-cultural community